Impact of experiential sustainability education on social enterpreneurial intentions - Ghosh, Tamanash (My University, 2019)
The field of social entrepreneurial intentions is rapidly evolving as an area of research. A total of 43 papers published in this area from 2008 to 2019 have tried to examine different variables that influence the process of forming SEIs. Our research further enriches this understanding by analysing the role of experiential sustainability education in influencing the formation of SEI.
Keywords: Social entrepreneurial intentions, social enterpreneurship, sustainability education